PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KUDUS TERHADAP PENARIKAN RETRIBUSI PARKIR DALAM RANGKA MENINGKATKAN PENDAPATAN DAERAH - Ramadhan, Ichsan (Jurnal Suara Keadilan, 2024)
Regional taxes and regional levies are Regional Original Income and one of the sources of regional income, funds obtained from regional taxes and levies are used to finance the running of the Regional Government. One of the Regional Original Income is from parking levies, the existence of parking lots in the city of Kudus has developed very significantly. This is in line with Kudus City as a kretek city and a city of religious tourism. Parking levies are one of the sources of Regional Original Income, which if parking levies are managed optimally, can increase Regional Original Income (PAD). This study will discuss the implementation of the Kudus Regency DPRD's supervisory function regarding the collection of parking levies as PAD and the level of intensity of the implementation of the Kudus Regency DPRD's supervisory function. This study uses a Non-Doctrinal problem approach method, the type of data in this study is primary data is data obtained or obtained directly from sources/informants, primary data is data that has not been processed or original data, therefore in order to be used primary data needs to be processed first. Secondary data is data that is ready and ready to be used. The data collection method in this study is primary data as the main data and secondary data as supporting data, data collection in this study by means of field studies (primary data) and literature studies (library research). Data analysis in this study by organizing and sorting data, organizing it into a pattern, category and basic description unit. The results of this research are that the supervisory function of the Regency DPRD to increase Regional Original Income includes supervision of the implementation of Regional Regulations and other statutory regulations, regional head regulations, regional government policies in implementing programs to increase Regional Original Income. The existence of illegal parking in Kudus Regency is the responsibility of the Parking UPT as the parking manager in Kudus Regency, and this problem must be resolved immediately by the Parking UPT. The effectiveness of implementing the supervisory function of the Regional People's Representative Council (DPRD) towards increasing regional legitimate income (PAD) can be carried out by implementing several monitoring methods, namely: Preliminary Control, Interim Control, and Post Control. Kudus Regency DPRD's supervision of Regional Original Revenue is not yet optimal, This is because there is still illegal parking.